Effect of Aureomycin and Rumensin on performance of finishing heifers - Jack G. Riley; Ronald V. Pope (Kansas Agricultural Experiment Station Research Reports, 1978)
We used 210 yearling Hereford heifers to evaluate the efficacy of Aureomycin and Rumensin fed alone and in combination. Each product is cleared by the FDA for use in feedlot rations as an individual feed additive, however, additional clearance must be obtained to use the two products in combination in the same ration. Aureomycin effectively controlled live abscessed, and Rumensin improve feed efficiency by 8.7%.
Keywords: Cattlemen' s Day; 1978; Report of progress (Kansas State University. Agricultural Experiment Station); 320; Beef; Aureomycin; Rumensin; Performance; Finishing heifers